Features of physical rehabilitation of the persons after a postered traumatic brain injury - Volodymyr Golyk (Kazimierz Wielki University, 2017)
The importance of studying the effects of traumatic brain injury is due to the fact that TBI is mainly noted in persons young and middle age, that is, the most active in the social and labor proportion of the population. The importance of studying this nosology determines high lethality, prolonged incapacity, as well as a variety of clinical manifestations. Purpose: Based on the study of the current state of the problem of recovery of patients with traumatic brain injury, to determine the features of physical rehabilitation of this category of persons. Methods of research: analysis, synthesis and generalization of scientific and methodical literature concerning the issue of restoration of functional capabilities of persons with traumatic brain injury. Results. Persons suffering from traumatic brain injury undergo physical, psychological, emotional and behavioral changes that require bio-psycho-social interception of rehabilitation interventions. The process of physical rehabilitation is aimed at increasing the tolerance to physical activity, improving vestibular oculomotor functions, level of balance and postural control, reducing the manifestations of cognitive impairment, which in turn will increase the activity of everyday life of patients. Conclusions. Physical rehabilitation of individuals allows to effectively realize and increase the functional potential of patients after a traumatic brain injury, using adequate means and methods in the process of recovery, and the main purpose of rehabilitation is to return the patient to work and social activity.